2017
DOI: 10.1177/1089253217708034
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cardiac Morbidity and Mortality in Patients With Aortic Valve Disease Following Liver Transplantation: A Case Matching Study

Abstract: Patients with pretransplant AV replacement or AS have significant cardiac complications (myocardial infarction, AV replacement, or cardiac death) in 1 to 3 years post-OLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A retrospective study does not find increased mortality in LT candidates with aortic stenosis (170). None of the patients in this study has severe aortic stenosis and LT is typically not offered to patients with severe aortic stenosis.…”
Section: Contrast-enhanced Echocardiography (Ce-tte)mentioning
confidence: 65%
“…A retrospective study does not find increased mortality in LT candidates with aortic stenosis (170). None of the patients in this study has severe aortic stenosis and LT is typically not offered to patients with severe aortic stenosis.…”
Section: Contrast-enhanced Echocardiography (Ce-tte)mentioning
confidence: 65%
“…Additionally, the severity of aortic stenosis has been found to correspond with perioperative mortality in patients undergoing noncardiac surgery[ 102 ]. Additionally, patients with uncorrected severe aortic stenosis undergoing LT have been found to have a higher rate of cardiac complications, including cardiac death, myocardial infarction, and requirement of aortic valve replacement in the post-transplant period compared to patients without valvular disease[ 101 , 103 ]. As per the AHA/ACC 2014 guidelines, elevated-risk elective noncardiac surgery is reasonable to perform in patients with either severe asymptomatic aortic stenosis, mitral regurgitation, or severe asymptomatic aortic regurgitation with normal LVEF[ 104 ].…”
Section: Clinical Entitiesmentioning
confidence: 99%
“…In a study looking at long-term cardiac morbidity and mortality in LT recipients with aortic valvular heart disease including those who have had valve replacement, it was observed that this group had significant cardiac complications that included myocardial infarction, postoperative SAVR, and cardiac death in 1 to 3 years post-OLT. 3 Since the first publication of combined AVR and LT in 2001, 4 only few cases have been reported. Transcatheter aortic valve implantation (TAVI) is currently the treatment modality of choice for patients with symptomatic severe AS who are inoperable or at high risk for SAVR.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first publication of combined AVR and LT in 2001, 4 only few cases have been reported. Transcatheter aortic valve implantation (TAVI) is currently the treatment modality of choice for patients with symptomatic severe AS who are inoperable or at high risk for SAVR.…”
Section: Introductionmentioning
confidence: 99%